2017
DOI: 10.1177/0892705717704485
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of penetration into Kevlar fabric impregnated with shear thickening fluid

Abstract: This study presents the high-velocity impact performance of a composite material composed of woven Kevlar fabric impregnated with a colloidal shear thickening fluids (STFs). Although the precise role of the STF in the high-velocity defeat, process is not exactly known but it is suspected to be due to the increased frictional interaction between yarns in impregnated fabrics. In order to explore the mechanism of this enhanced energy absorption, high-velocity impact test was conducted on neat, impregnated fabric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…The mechanisms that dominate a particular ballistic event depend on a number of factors, including yarn's material properties [9,10], friction between yarns [11,12], the projectile shape [13,14], and fabric boundary condition [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms that dominate a particular ballistic event depend on a number of factors, including yarn's material properties [9,10], friction between yarns [11,12], the projectile shape [13,14], and fabric boundary condition [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…With this understanding in mind, many researchers worked towards improving the friction by using resins, polymeric coatings and additives such as nanostructures for more energy absorption. 31 As a matter of fact, the use of STF itself, as believed by many researchers 32,33 helps in improved performance majorly through friction enhancement. Nanorods of metal oxides are also used to intensify friction between yarns.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…26 It is well grounded that increased inter-yarn friction improves the pull-out force, and hence the energy absorption. [27][28][29][30][31][32][33][34][35][36] Bazhenov 28 concluded that the dissipation of energy increases with the increase in pull-out zone dimensions. The latter, in turn, depends upon the increased involvement of more and more secondary yarns which is a direct positive consequence of yarn to yarn friction.…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…High velocity impact-resistant materials attract the attention for the past few decades [12][13][14]. Impact performance is one of the major concerns in many polymer applications.…”
mentioning
confidence: 99%